2015
DOI: 10.1103/physrevd.92.083009
|View full text |Cite
|
Sign up to set email alerts
|

Four-hair relations for differentially rotating neutron stars in the weak-field limit

Abstract: The opportunity to study physics at supra-nuclear densities through X-ray observations of neutron stars has led to in-depth investigations of certain approximately universal relations that can remove degeneracies in pulse profile models. One such set of relations determines all of the multipole moments of a neutron star just from the first three (the mass monopole, the current dipole and the mass quadrupole moment) approximately independently of the equation of state. These three-hair relations were found to h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 77 publications
(122 reference statements)
1
24
0
Order By: Relevance
“…Completely analytic three-hair relations can also be obtained if one studies stars with equations of state that are perturbations from n = 0 polytropes [174,176]. Doing so, one finds that [174,175]…”
Section: Newtonian Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Completely analytic three-hair relations can also be obtained if one studies stars with equations of state that are perturbations from n = 0 polytropes [174,176]. Doing so, one finds that [174,175]…”
Section: Newtonian Resultsmentioning
confidence: 99%
“…The first (and only) study of the no-hair relations in differentially-rotating stars is that of Bretz et al [175], which restricts attention to the Newtonian limit and the small differential-rotation limit. Although the actual profile of rotation depends on the astrophysical situation one considers, the rotation law in the Newtonian limit can be parametrized in a generic way as [189] Ω Ω c =…”
Section: Differential Rotationmentioning
confidence: 99%
“…Another idea one could explore in the future is whether the universality we have found is robust to the inclusion of strong magnetic fields or rapid rotation. In the I-Love-Q case, the universality was found to be robust to the latter for a fixed dimensionless spin angular momentum [5,7,32], but not to the former [33], thus breaking in proto-neutron stars (see [34,35] for related work) and in magnetars (but not in millisecond pulsars). One may expect the same to be true for the entropy of neutron stars, but this should be verified through numerical calculations.…”
Section: Musings and Future Directionsmentioning
confidence: 98%
“…Although the focus of our paper is for WDs, we here comment on how differential rotation, finite temperatures and deviations from chemical equilibrium affect the I-Love-Q relations for NSs. The effect of differential rotation on universal relations 2 has been studied in (Bretz et al 2015) within the Newtonian limit and small differential-rotation approximation. The authors showed that the fractional difference in the relations from the uniformly-rotating case is comparable to the fractional amount of differential rotation over uniform rotation.…”
Section: Discussionmentioning
confidence: 99%
“…The universal relations studied in(Bretz et al 2015) were those among stellar multipole moments rather than the I-Love-Q relations.…”
mentioning
confidence: 99%